ANALISA KEBIJAKAN PENGENDALIAN KONVERSI LAHAN DI JAWA TENGAH (TAHUN 1995-2005) - Widayati, Wiwik (JURNAL ILMU SOSIAL, 2013)
In Central Java the conversation of wetland area toward non agricaltural used results in he decrease of food production. Beside, there would be the lose some other crucial wetland functions such of environment and social functions. However land conversation was unadvoidable, although there are many government regulation to control land conversation, the effectiveness of there regulation can not be sustainable due to weakness of the legal system, low commitment of the government and the law people’s awareness of their rights and obligation in the uses of land.